2019
DOI: 10.1055/s-0039-1692992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Radiologic, Arthroscopic, and Clinical Outcomes between Repaired versus Unrepaired Medial Meniscus Posterior Horn Root Tear During Open Wedge High Tibial Osteotomy

Abstract: The efficacy and outcomes for the concurrent repair of medial meniscus posterior horn root tear (MMPHRT) during open wedge high tibial osteotomy (OWHTO) are unclear. This study compared the radiologic, arthroscopic, and clinical outcomes between repaired and unrepaired MMPHRT during OWHTO. Fifty-seven patients were prospectively enrolled from 2014 to 2016. The radiologic, arthroscopic, and clinical outcomes were compared between 25 patients who underwent OWHTO with all-inside repair of MMPRT using FasT-Fix (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 48 publications
3
43
1
Order By: Relevance
“…33,34 However, at the present time, there is a paucity of studies comparing the outcomes of solely OWHTO and OWHTO concomitant with meniscus posterior root repair, while a few studies showed that significant differences of the clinical and radiologic outcomes were not found between the procedures. 35,36 There is insufficient evidence to exclude the possibility that the meniscus root tear and meniscus root repair influenced the results of the present study.…”
Section: Discussionmentioning
confidence: 78%
“…33,34 However, at the present time, there is a paucity of studies comparing the outcomes of solely OWHTO and OWHTO concomitant with meniscus posterior root repair, while a few studies showed that significant differences of the clinical and radiologic outcomes were not found between the procedures. 35,36 There is insufficient evidence to exclude the possibility that the meniscus root tear and meniscus root repair influenced the results of the present study.…”
Section: Discussionmentioning
confidence: 78%
“…A total of 7 studies 17 , 28 , 31 , 36 , 37 , 55 , 69 reported the BMI of the patients. When the BMI was ≥26, the complete healing rate was 64% (177/260 knees; 95% CI, 49%-76%; I 2 = 78%), the partial healing rate was 12% (47/260 knees; 95% CI, 2%-43%; I 2 = 94%), and the failure rate was 13% (36/260 knees; 95% CI, 8%-21%; I 2 = 54%).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been shown that meniscal root tears lead to the loss of circumferential hoop stresses, and strongly correlate with progressive symptomatic joint arthritis [9]. Therefore, most of the studies indicated that surgery should be recommended for patients with high demands and no to low-grade osteoarthritis [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…At the nal follow-up, radiologic outcomes of the repaired meniscus healing status were assessed by orthopedic surgeons and radiologist using knee MRI according to the criteria of previous studies [9][10][11].…”
Section: Outcome Assessmentmentioning
confidence: 99%